Anesthesia Depth Measurement with Bispectral Index Monitoring during Minor Surgery among Children With and Without Cerebral Palsy - Chavoshi, Tahereh; Mahdavi, Seyed Alireza; Razavi, Seyed Sajad; Shafa, Amir; Hajipour, Mahmoud; Mahdavi, Nastaran Sadat; Moshari , Mohammadreza (Iranian Journal of Pediatric Surgery, 2021)
Introduction: Unfortunately, few studies have been performed on the pharmacodynamic effects of anesthesia in children suffering cerebral palsy(CP).Patients were candidates for surgeryfor various reasons. Due to the lower need for anesthesiain these children, side effects of various anesthetic agents, adverse drug reactions, delayed awareness and higher costs can be prevented in these children. The present study aims to evaluate and compare the depth of anesthesia in minor surgeries using Bispectral Index (BSI) in children sufferingCP. Materials and Methods: This cohort study was performed on 64 children aged two to ten years in two groups with and without cerebral palsy inMofid Hospital, Tehran, Iran in 2020. BIS index, mean arterial blood pressure and heart rate were measured before and after anesthesia induction, every ten minutes during operation, after extubation and when being able to respond to verbal stimulation. Results: This studyexamined 64 patients equally divided into two study groups “with and without cerebral palsy”. The mean BIS level in children suffering CP was lower than children without cerebral palsy. The dosage of isoflurane gas used for anesthesia in CPpatientswas meaningfully lower than itsdosage in children without cerebral palsy. Conclusion: Monitoring of anesthesia in this study, showed that use of BIS could reduce the use of anesthetic agents and related side effects to provide the appropriate depth of anesthesia.